Impact of internal locus of control through self-efficacy variables on employee performance (study of employees of the false eyelash production section of PT. Tiga Putra Abadi Perkasa in Purbalingga Regency) - Wardani, Shanti Ike; Hadi, Sudharto P.; Nugraha, Hari S. (Institute of Computer Science (IOCS), 2024)
Employee's performance of PT. Tiga Putra Perkasa Abadi showed by the average output per employee is fluctuating. Factors that affect performance are internal locus of control and self-efficacy. The aim of this study was to determine and analyze the influence of internal variables locus of control and self-efficacy on employee performance in partial and self-efficacy as an intervening variable. A type of this research is explanatory research, the population of all the production employees of PT. Tiga Putra Perkasa Abadi are 450 people and the sample size is 90 people by random sampling technique. A questionnaire is used to collect the research data and SEM-PLS to analyze the data. Analysis tool of this data is SmartPLS 3.0. The results of this coefficient SEM analysis revealed that: (1) internal locus of control variable to self efficacy has tcount> ttable = 2.985 ˃ 1.96 and the significance was 0.003 ˂ 0.05, the hypothesis is accepted; (2) self-efficacy variable to the performance of employees has tcount> ttable = 2.438 ˃ 1.96 and the significance was 0.013 ˂ 0.05, the hypothesis is accepted; (3) internal locus of control variable to employees performance has tcount> ttable = 2.262 ˃ 1.96 and the significance was 0.024 ˂ 0.05, the hypothesis is accepted; (4) internal locus of control variable to employee performance through self efficacy has tcount < ttable = 1.895 < 1.96 and the significance was 0.059 > 0.05, the hypothesis is rejected. Results of this study showed that were some weak indicators of each variable, so it is advisable to monitor and evaluate the company as well as provide training and personal development of employees to improve the employees' abilities.